2021
DOI: 10.1002/mgg3.1615
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating political power and stigma around fragile X Syndrome in a rural village in Cameroon: A tale of a royal family and a community

Abstract: Background Fragile X Syndrome (FXS) is a neurogenetic condition that significantly impacts the lives of affected individuals and their families due to its association with intellectual disability (ID) and stigma. Method In this paper, we present the findings of an ethnographic study in the community of a patient who received a genetic diagnosis for FXS in Cameroon. This study builds on data from 28 participants of a royal family and 58 from the community who participated in 20 in‐depth interviews and nine focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…This stigma from cultural beliefs may hinder early identification and testing because families and or communities may conceal affected individuals to prevent alienation by unaffected community members. Kamga et al [ 94 ] in their qualitative study in Cameroon reported the experience of a mother who had two children with FXS. She was a descendant of the founder of a powerful royal family and despite this, they clearly experienced stigma, isolation, and name-calling.…”
Section: Epidemiology Of Fxs In Africamentioning
confidence: 99%
“…This stigma from cultural beliefs may hinder early identification and testing because families and or communities may conceal affected individuals to prevent alienation by unaffected community members. Kamga et al [ 94 ] in their qualitative study in Cameroon reported the experience of a mother who had two children with FXS. She was a descendant of the founder of a powerful royal family and despite this, they clearly experienced stigma, isolation, and name-calling.…”
Section: Epidemiology Of Fxs In Africamentioning
confidence: 99%